2013
DOI: 10.1002/glia.22572
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid (LPA) and its receptor, LPA1, influence embryonic schwann cell migration, myelination, and cell-to-axon segregation

Abstract: Schwann cell (SC) migration is an important step preceding myelination and remyelination in the peripheral nervous system, and can be promoted by peptide factors like neuregulins. Here we present evidence that a lipid factor, lysophosphatidic acid (LPA), influences both SC migration and peripheral myelination through its cognate G protein-coupled receptor (GPCR) known as LPA1. Ultrastructural analyses of peripheral nerves in mouse null-mutants for LPA1 showed delayed SC-to-axon segregation, polyaxonal myelinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 55 publications
3
64
0
1
Order By: Relevance
“…Moreover, in zebrafish, enpp2 regulates the commitment of olig2-expressing progenitors into lineage committed oligodendrocyte progenitors, supporting the role for LPA in this process (Yuelling et al, 2012). In the mouse peripheral nervous system, Schwann cells depend upon LPA signalling for both survival (Contos et al, 2000;Weiner and Chun, 1999) and proper myelination (Anliker et al, 2013;Weiner et al, 2001), and they express Lpar1, Lpar4 and Lpar6 (Anliker et al, 2013). Microglia are the resident macrophages of the CNS and have developmental roles (Innocenti et al, 1983).…”
Section: Lpa In the Nervous Systemmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, in zebrafish, enpp2 regulates the commitment of olig2-expressing progenitors into lineage committed oligodendrocyte progenitors, supporting the role for LPA in this process (Yuelling et al, 2012). In the mouse peripheral nervous system, Schwann cells depend upon LPA signalling for both survival (Contos et al, 2000;Weiner and Chun, 1999) and proper myelination (Anliker et al, 2013;Weiner et al, 2001), and they express Lpar1, Lpar4 and Lpar6 (Anliker et al, 2013). Microglia are the resident macrophages of the CNS and have developmental roles (Innocenti et al, 1983).…”
Section: Lpa In the Nervous Systemmentioning
confidence: 83%
“…LPA signalling influences the survival, proliferation, differentiation, migration, adhesion and morphology of a range of cell types during development. These include neural progenitor cells (NPCs), astrocytes and oligodendrocytes in the nervous system (Anliker et al, 2013;Fukushima et al, 2002), endothelial cells during vascular formation and maintenance (Chen et al, 2013;Yukiura et al, 2011), cells of the reproductive system (Ye and Chun, 2010), osteoblasts and osteoclasts during bone development (Lapierre et al, 2010;Liu et al, 2010), proliferating pre-adipocytes (Valet et al, 1998), and cells of the immune system (Chan et al, 2007;Goetzl et al, 2000;Zhang et al, 2012). Here, we review how LPA is produced and metabolised during development, how it signals and how it influences the development of a number of tissues and organs.…”
Section: Introductionmentioning
confidence: 99%
“…Peripherally, a recent study has showed the involvement of the LPA 1 receptor in Schwann cell migration and nerve development, including myelination, in sciatic nerves (Anliker et al 2013). Notwithstanding these studies, the function of LPA 1 receptor in brain myelination remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 97%
“…The LPA1 ligand, lysophosphatidic acid (LPA), is produced by neurons and is a potent survival and migration factor for Schwann cells in culture [40,41]. Analysis of Lpa1 knockout mice demonstrate that this receptor is required for Schwann cell survival, radial sorting, and proper myelination in vivo [40,41].…”
Section: Gpcrs In Schwann Cell Development and Myelinationmentioning
confidence: 99%
“…The LPA1 ligand, lysophosphatidic acid (LPA), is produced by neurons and is a potent survival and migration factor for Schwann cells in culture [40,41]. Analysis of Lpa1 knockout mice demonstrate that this receptor is required for Schwann cell survival, radial sorting, and proper myelination in vivo [40,41]. The role of axon-Schwann cell GPCR signaling in controlling radial sorting also likely extends to other players, given that neuronally-derived Wnt and Respondins may also signal via Lgr receptors and Lrp/Frizzled receptor complexes on Schwann cells [42].…”
Section: Gpcrs In Schwann Cell Development and Myelinationmentioning
confidence: 99%